2018
DOI: 10.3389/fendo.2018.00496
|View full text |Cite
|
Sign up to set email alerts
|

Links Between Obesity-Induced Brain Insulin Resistance, Brain Mitochondrial Dysfunction, and Dementia

Abstract: It is widely recognized that obesity and associated metabolic changes are considered a risk factor to age-associated cognitive decline. Inflammation and increased oxidative stress in peripheral areas, following obesity, are patently the major contributory factors to the degree of the severity of brain insulin resistance as well as the progression of cognitive impairment in the obese condition. Numerous studies have demonstrated that the alterations in brain mitochondria, including both functional and morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 185 publications
(325 reference statements)
1
79
0
Order By: Relevance
“…It has been demonstrated that consumption of a high-calorie diet intake enhanced oxidative stress in several tissues, including brain tissue [34,49]. Similarly, others also demonstrated that consumption of HFD significantly reduced the protein expression level of hemeoxygenase-1 (HO-1) and nuclear factor-2 erythroid-2 (Nrf-2) in HFD-fed mice brains [28].…”
Section: Hfd Induces Oxidative-stress-mediated Brain Insulin Resistanmentioning
confidence: 96%
“…It has been demonstrated that consumption of a high-calorie diet intake enhanced oxidative stress in several tissues, including brain tissue [34,49]. Similarly, others also demonstrated that consumption of HFD significantly reduced the protein expression level of hemeoxygenase-1 (HO-1) and nuclear factor-2 erythroid-2 (Nrf-2) in HFD-fed mice brains [28].…”
Section: Hfd Induces Oxidative-stress-mediated Brain Insulin Resistanmentioning
confidence: 96%
“…Several pathophysiological links have been demonstrated between AD and metabolic disorders such as T2DM, obesity and metabolic syndrome [ 31 , 32 , 33 ]. In contrast to a small subset of AD cases (~3%) attributable to inherited genetic causes, the pathogenesis and aetiology of sporadic, late onset AD (LOAD) are multifactorial, involving genetic and life-style risk factors [ 34 ].…”
Section: T2dm and Neurodegeneration: The Role Of Impaired Insulinmentioning
confidence: 99%
“…Important pathogenetic features of dopaminergic nigral neuron degeneration in PD include the accumulation of α-synuclein (SNCA) and mitochondrial dysfunction [13]. Diabetes and cellular IR are strongly linked with systemic mitochondrial dysfunction, including in neurons [14,15]. Impaired mitochondrial biogenesis, depolarization of mitochondrial membrane potential, and increased reactive oxygen species (ROS) have been reported in neuronal cells with IR [16].…”
Section: Introductionmentioning
confidence: 99%